Individual constraints for information structure - Song, Sanghoun; Bender, Emily M. (Proceedings of the 19th International Conference on Head-Driven Phrase Structure Grammar, 2012)
This paper, in the context of multilingual MT, proposes the use of ICONS(Individual CONstraintS) to add a representation of information structure toMRS. The value of ICONS is a list of objects of type info-str, each of whichhas the features CLAUSE and TARGET. The subtypes of info-str indicatewhich information structural role is played by the TARGET with respectto the CLAUSE. This proposal is designed to support both the calculationof focus projection from underspecified representations and the handling ofmulticlausal sentences.